2013
DOI: 10.1093/schbul/sbt077
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Brain Network Connectivity Indicates Degree of Both Schizophrenia Risk and Cognitive Dysfunction

Abstract: Objective: Cognitive dysfunction is a core feature of schizophrenia, and persons at risk for schizophrenia may show subtle deficits in attention and working memory. In this study, we investigated the relationship between integrity of functional brain networks and performance in attention and working memory tasks as well as schizophrenia risk. Methods: A total of 235 adults representing 3 levels of risk (102 outpatients with schizophrenia, 70 unaffected first-degree relatives of persons with schizophrenia, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 100 publications
1
38
0
Order By: Relevance
“…When we restricted the hippocampal seed to anterior hippocampus, dysconnected regions shifted more anteriorly, including anterior cingulate and the medial prefrontal cortex, as well as the superior temporal gyrus, thalamus and precuneus. Results illustrate dysconnectivity patterns with regions that are primarily impacted by previously reported alterations in hippocampal structure and activity (Shergill et al, 2000; Kircher et al, 2001; Shergill et al, 2003; Seiferth et al, 2008; Wolf et al, 2009; Cronenwett and Csernansky, 2010; Preston et al, 2010; Faget-Agius et al, 2012; Arnold et al, 2014; Unschuld et al, 2014; Anticevic et al, 2014; van Tol et al, 2014; Lui et al, 2014; Mathew et al, 2014). These present results lend support to the hypothesis that cerebral dysfunction in psychotic illnesses derives from hippocampal dysfunction.…”
Section: Discussionmentioning
confidence: 59%
“…When we restricted the hippocampal seed to anterior hippocampus, dysconnected regions shifted more anteriorly, including anterior cingulate and the medial prefrontal cortex, as well as the superior temporal gyrus, thalamus and precuneus. Results illustrate dysconnectivity patterns with regions that are primarily impacted by previously reported alterations in hippocampal structure and activity (Shergill et al, 2000; Kircher et al, 2001; Shergill et al, 2003; Seiferth et al, 2008; Wolf et al, 2009; Cronenwett and Csernansky, 2010; Preston et al, 2010; Faget-Agius et al, 2012; Arnold et al, 2014; Unschuld et al, 2014; Anticevic et al, 2014; van Tol et al, 2014; Lui et al, 2014; Mathew et al, 2014). These present results lend support to the hypothesis that cerebral dysfunction in psychotic illnesses derives from hippocampal dysfunction.…”
Section: Discussionmentioning
confidence: 59%
“…We plan to pursue this approach. In addition, the assumption here is that the correlation trends between the imaging maps and MCCB scores would be similar in both groups, in consistent with (81, 82), whereas our method also allows patients and controls to exhibit opposite correlations between imaging signatures and cognition by separately calculating correlations within each group, as shown in (83). In future studies with more subjects and greater statistical power or with task-related fMRI, we may expect to find such relationships.…”
Section: Discussionmentioning
confidence: 80%
“…In particular, SZ patients showed more severe and pervasive cognitive deficits while BD patients present a milder and more confined impairment. Prior B-SNIP analysis showed that the excessive connectivity within brain networks coupled to the dlPFC and medial PFC was associated with cognitive deficits in persons at risk for SZ (Unschuld et al, 2014). We found a modest association between brain signal randomness in the dorsal or ventral PFC and the BACS digit span.…”
Section: Discussionmentioning
confidence: 99%